Diffuse to fuse EEG spectra – Intrinsic geometry of sleep dynamics for classification - Liu, Gi-Ren; Lo, Yu-Lun; Malik, John; Sheu, Yuan-Chung; Wu, Hau-Tieng (Biomedical signal processing and control, 2020)
•Combine scattering transform and diffusion map to analyze a single channel EEG signal.•Apply multiview diffusion map to fuse two EEG channels.•Novel sleep dynamics features based on 1 and 2 for automatic sleep annotation.•Provide state-of-the-art automatic annotation results on the benchmark databases.•The proposed algorithm has solid theoretical backups. We propose a novel algorithm for sleep dynamics visualization and automatic annotation by applying diffusion geometry based sensor fusion algorithm to fuse spectral information from two electroencephalograms (EEG). The diffusion geometry approach helps organize the nonlinear dynamical structure hidden in the EEG signal. The visualization is achieved by the nonlinear dimension reduction capability of the chosen diffusion geometry algorithms. For the automatic annotation purpose, the support vector machine is trained to predict the sleep stage. The prediction performance is validated on a publicly available benchmark database, Physionet Sleep-EDF [extended] SC* (SC = Sleep Cassette) and ST* (ST = Sleep Telemetry), with the leave-one-subject-out cross validation. When we have a single EEG channel (Fpz-Cz), the overall accuracy, macro F1 and Cohen's kappa achieve 82.72%, 75.91% and 76.1% respectively in Sleep-EDF SC* and 78.63%, 73.58% and 69.48% in Sleep-EDF ST*. This performance is compatible with the state-of-the-art results. When we have two EEG channels (Fpz-Cz and Pz-Oz), the overall accuracy, macro F1 and Cohen's kappa achieve 84.44%, 78.25% and 78.36% respectively in Sleep-EDF SC* and 79.05%, 74.73% and 70.31% in Sleep-EDF ST*. The results suggest the potential of the proposed algorithm in practical applications.